Konsep Pendidikan Sufistik Menurut Syeh Abu Hasan Asy-Sadzily (Tela’ah Kitab Risalatul Amin Fi Wusuli Li Robbil Alamin) - Muhammad Rizal Ansori; Duski Ibrahim; Munir Munir (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
Development of technology has an impact on high intellectuality, but beside it is also low morality and spirituality. This condition important to revitalization religious education and a self-approach to Allah SWT namely Sufism education. The formation of religious, steady and stable human beings. This is a qualitative research and including in library research, the approach used is the thought of figure, and the object of this research is Sufism . The purpose of this study is to achieve a comprehensive understanding of Sheikh Abul Hasan asy-Syadzili thoughts, founder of a Syadziliyah order of mystics. Results of this research is morality-amali Sufism education of Sheikh Abul Hasan asy-Syadzili. His thinking is influenced by Sufism and thinkers previous him, especially al Imam Ghazali and Sufisms implementer. Second, the basic concept of Sufism education in Risalatul Amin fi Wusuli Li Robbil Alamin's book can be classified into four categories, that is remembrance, thinking (tafakur), really need (faqir), and love. Characteristics Sufism of Sheikh Abul hasan is flexibility. He said, Sufism is not have to away from the worldly, but true Sufism are associate with society and resolve their problem, true Sufism are have treasure but they are not controlled by it.